DSP Integration of Sound Source Localization and Multi-channel Wiener Filter - Lee, Byoung-gi; Kim, Hyun-dong; Choi, Jong-suk; Kim, Seyun; Cho, Nam Ik (2010 IEEE INTERNATIONAL CONFERENCE ON ROBOTICS AND AUTOMATION (ICRA), 2010)
This paper describes a DSP integration of sound source localization (SSL) and multi-channel Wiener filter (MWF). To develop a robot audition system, we integrated SSL module and MWF module into a DSP system. SSL is a module to perceive the direction of a human user's call. It measures time delay of arrival among microphones and estimates the direction of sound source. Also, it post-processes the resulted estimations of direction by histogram to perceive the direction robustly under noisy environment. MWF is a module to reduce background noises from raw voice signal to enhance the performance of robot's speech recognition. It gathers information of background noises during noise-period and then reduces noises during voice-period. This SSL-MWF combination system will be a cheap, high-performing and convenient solution for robot audition.